Simulasi Penggunaan Rounding Front Hood Kendaraan Terhadap Pola Aliran Dan Distribusi Koefisien Tekanan Pada Upperside Kendaraan Model - Marbun, Pajar Doli Soripada; Suryawan, Anak Agung Adhi; Karohika, I Made Gatot (Teknik Desain Mekanika, 2024)
Abstract Vehicles have become a daily necessity, leading to a high demand for vehicles. Consequently, fuel consumption has increased, while oil fuel is a non-renewable resource. Therefore, innovations in vehicles to achieve fuel efficiency are highly needed in order to save oil fuel. One of these innovations is the rounding of the front hood of a vehicle, aimed at reducing vortexes in the airflow passing through the car and minimizing drag coefficients. It also involves examining the pressure distribution on the upper side of the vehicle, which experiences significant pressure from the airflow. The aerodynamic forces on a vehicle are partly caused by pressure on the body surface. This study utilizes Computational Fluid Dynamics (CFD) simulations using a sedan vehicle model, with variations in the rounding of the front hood, including no rounding and a 400 mm rounding. The vehicle models are simulated at a speed of 80 km/h. The results indicate that the airflow pattern passing through the rounding vehicle still exhibits a significant forward bound vortex at the front, whereas the vehicle model with a 400 mm rounding has a reduced forward bound vortex. As a result, the drag coefficient obtained is smaller than that of the vehicle model without rounding, with a difference in drag coefficient of 0.10232696. Stagnation points occur in the vehicle model without rounding and the vehicle with a 400 mm rounding at x=0, while separation points occur at x=0.1 in the vehicle without rounding and at x=1.825 in the vehicle with a 400 mm rounding. Keywords: Computational Fluid Dynamics, Drag Coefficient, Pressure Coefficient, Airflow Patterns